From client to co-worker: a case study of the transition to peer work within a multi-disciplinary hepatitis c treatment team in Toronto, Canada - Paula Tookey; Kate Mason; Jennifer Broad; Marty Behm; Lise Bondy; Jeff Powis (BMC, 2018)
Abstract Background Despite the integration of peer workers into harm reduction services, there is little documentation regarding the experience of this integration or of models in which peers are fully integrated as members of health care teams. The purpose of this study was to gain an in-depth understanding of the transition from client to support worker from the perspective of two individuals who received treatment for hepatitis C at a multi-disciplinary, community-based program, grounded in a harm reduction approach to substance use. Methods A participatory case study design was selected. Interviews were conducted with two current peer workers who were also involved in the study design, analysis and writing. Data was coded and analyzed using an inductive approach to identify emergent themes. Results Five primary themes emerged during our analysis of the facilitators and challenges of the transition from client to support worker: (1) the role of prior experience, (2) changes in substance use practices, (3) shifts in relationships with community members and friends, (4) supportive organizational and structural factors, and (5) role transition as a journey. In some cases, themes overlapped and contained elements that were both facilitating and challenging. Conclusions The transition from client to co-worker is a gradual process and one that is supported by, and in turn helps to support, a number of other personal transitions. The cases examined here suggest that a model of peer employment with broad qualification criteria, sufficient transition timelines, flexible job responsibilities, a solid investment in the inclusion of people with lived experience, and a harm reduction framework will support successful integration of current and/or former clients into health care teams.